VIRTUALIZATION TECHNOLOGIES SYSTEMATIZATION - Golovnya, О.С. (Journal of Information Technologies in Education (ITE), 2012)
The paper advices a generalized variant of virtualization technologies systematization. The concerned variant has been constructed of quite a number of variants and aims to reveal relations between numerous existing terms, including synonymous ones, and may be used in scientific research of virtualization and in the design of methodological support for bachelors of informatics.